2007
DOI: 10.1111/j.1399-3046.2007.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Dyskeratosis congenita: Advances in the understanding of the telomerase defect and the role of stem cell transplantation

Abstract: DC is a multisystem bone marrow failure syndrome exhibiting marked clinical and genetic heterogeneity. X-linked, autosomal dominant and autosomal recessive subtypes are recognized. The gene mutated in X-linked DC (DKC1) encodes a highly conserved nucleolar protein called dyskerin. Dyskerin associates with the H/ACA motif class of small nucleolar RNAs in small nucleolar ribonucleoprotein particles that are important in guiding the conversion of uracil to pseudouracil during the maturation of ribosomal RNA. Dysk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 43 publications
3
111
0
1
Order By: Relevance
“…Previous reports (Table 3) have described progression of the clinical signs of DKC after transplantation, which was indistinguishable from the natural course of disease. [8][9][10][11][20][21][22][23] In our series, all patients except one received low intensity conditioning regimens. The conditioning protocol was different across different centers.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous reports (Table 3) have described progression of the clinical signs of DKC after transplantation, which was indistinguishable from the natural course of disease. [8][9][10][11][20][21][22][23] In our series, all patients except one received low intensity conditioning regimens. The conditioning protocol was different across different centers.…”
Section: Discussionmentioning
confidence: 86%
“…Commonly observed transplant-related problems include graft failure, GVHD, sepsis and, more importantly, the increased propensity to develop organ toxicity, namely pulmonary fibrosis, hepatic cirrhosis and veno-occlusive disease, among others. [8][9][10] As a result, long-term survival of persons with DKC following HSCT has been poor. Reduced intensity preparative regimens are less likely to cause organ toxicity and may improve long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Bone marrow failure along with pulmonary complications and malignancies are all common causes of premature death in patients with DC as well as a myriad of other abnormalities. 2,3 Hematopoietic stem cell transplantation (HSCT) with fully myeloablative regimens has historically been the only curative treatment. 2,3 Attempts at reducing morbidity and mortality post HSCT with reduced intensity conditioning regimens instead of myeloablative regimens have been reported, and over the past decade, experience treating DC associated marrow failure with reduced intensity HSCT has increased.…”
mentioning
confidence: 99%
“…Patients with BMF due to DC do not respond to immunosuppressive therapy [45]. They are also at high risk of HSCT-related complications due to underlying pulmonary and liver disease [46][47][48][49][50]. In addition, recent studies have shown individuals can be "silent" carriers of a pathogenic mutation in a DC gene [12].…”
Section: Making the Diagnosismentioning
confidence: 99%
“…HSCT is clearly a life-saving measure, but has substantial risks either from toxicity from radiochemotherapy or immune-related complications. Reported problems include graft failure, GVHD, sepsis, pulmonary fibrosis, cirrhosis, and veno-occlusive disease [49;66], due, in part, to underlying pulmonary and liver disease [46][47][48][49][50]. As a result, long-term survival of patients with DC following HSCT has been very poor [49;66].…”
Section: Medical Management Of Dyskeratosis Congenitamentioning
confidence: 99%